Crimes against Justice under the Legislation of the States of the European Union - Vorobchak, Andrii R.; Nalutsyshyn, Viktor V.; Nalutsyshyn, Volodymyr V.; Popovych, Olena V. (International Journal of Criminology and Sociology, 2022)
The countries of the European Union (EU) are united, but above all, each country is autonomous. EU Member States have different legislation on criminal offences. The EU authorities have already suggested the possibility of creating a single system for regulating legal provisions on criminal offences. Studying and comparing the legal systems and responsibilities for crimes against justice in individual countries will facilitate the analysis of the differences in the legislation of the EU countries. The purpose of this paper is to investigate crimes against justice in accordance with the laws of each individual European country. The paper considers the composition of such crimes, as well as the responsibility to which offenders can be brought in case of such crimes. The study uses the methods of analysis and synthesis, analyses legal provisions. General methods of scientific cognition used in this study include dialectical, historical, the Aristotelian method, method of systematic data analysis, formal legal method, method of legal modelling and comparative legal method. The study investigates the legal framework of European countries, in particular criminal codes and laws. This study systematises and groups the received information and data on criminal liability of judges for unlawful decisions. The European practices in punishing those who do not comply with court rulings and judgments are also analysed. A study of the legal system in individual EU countries will help distinguish between positive and negative aspects in the legislation. In addition, this study allows to consider and analyse the most effective laws, provisions, and principles that can be implemented in the current legal system of different countries of the world.